Results 1 to 3 of 3

Math Help - Binomial Expansion

  1. #1
    Member srirahulan's Avatar
    Joined
    Apr 2012
    From
    Srilanka
    Posts
    173

    Binomial Expansion

    C{_0}^{2}+C{_1}^{2}+C{_2}^{2}+...............+C{_0  }^{2}=\frac{2n!}{n!^2}

     C{_0}^{2} - C{_1}^{2}+C{_2}^{2} - C{_3}^{2}+..........+(-1)C{_n}^{n}=\frac{(-1)^{\frac{n}{2}}n!}{n/2)!^2} ---->>> (n even number)
    =0 --------------------------------------------------------->>>>(n odd number)

    i use binomial expansion theorem but i cannot get the answer like this.....please give me hint for these problems>>>><<<<
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor
    Joined
    Nov 2010
    Posts
    1,881
    Thanks
    743

    Re: Binomial Expansion

    Your notation is not at all standard. I will help you rewrite it. Press Reply With Quote to see how I did it.

    \binom{n}{0}^2 + \binom{n}{1}^2 + \binom{n}{2}^2 + \cdots + \binom{n}{n}^2 = \binom{2n}{n} = \dfrac{(2n)!}{(n!)^2}

    \binom{n}{0}^2 - \binom{n}{1}^2 + \binom{n}{2}^2 - \binom{n}{3}^2 \pm \cdots + (-1)^n\binom{n}{n}^2 = \begin{cases}\dfrac{(-1)^{n/2}n!}{[(n/2)!]^2} & n\text{ is even} \\ 0 & n\text{ is odd}\end{cases}

    For the first one,

    \sum_{k=0}^{2n}\binom{2n}{k}x^k = (1+x)^{2n} = (1+x)^n(1+x)^n = \left(\sum_{k=0}^n \binom{n}{k}x^k \right)^2

    For the coefficient of x^n, you have \binom{2n}{n} on the LHS. On the RHS, you need to multiply out first. Each term will be of the following form: \binom{n}{k_1}x^{k_1}\binom{n}{k_2}x^{k_2} = \binom{n}{k_1}\binom{n}{k_2}x^{k_1+k_2}. So, you want to add up all terms where k_1+k_2 = n. That means k_2 = n-k_1. So,

    \binom{2n}{n} = \binom{n}{0}\binom{n}{n-0} + \binom{n}{1}\binom{n}{n-1} + \cdots + \binom{n}{n-1} \binom{n}{n-(n-1)} + \binom{n}{n}\binom{n}{n-n}

    Since \binom{n}{k} = \binom{n}{n-k} for all k, you can rewrite the RHS as:

    \binom{n}{0}\binom{n}{0} + \cdots + \binom{n}{n}\binom{n}{n} = \binom{n}{0}^2 + \cdots + \binom{n}{n}^2
    Follow Math Help Forum on Facebook and Google+

  3. #3
    MHF Contributor
    Joined
    Nov 2010
    Posts
    1,881
    Thanks
    743

    Re: Binomial Expansion

    For the second one, do something similar with \sum_{k=0}^n (-1)^k\binom{n}{k}x^{2k} = (1-x^2)^n = (1+x)^n(1-x)^n = \left(\sum_{k=0}^n \binom{n}{k}x^k\right)\left(\sum_{k=0}^n (-1)^k\binom{n}{k}x^k\right). Again, find the coefficient of x^n on each side.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Binomial Expansion
    Posted in the Discrete Math Forum
    Replies: 6
    Last Post: May 3rd 2011, 08:18 PM
  2. binomial expansion
    Posted in the Pre-Calculus Forum
    Replies: 1
    Last Post: November 9th 2009, 04:07 PM
  3. Binomial expansion help
    Posted in the Algebra Forum
    Replies: 2
    Last Post: June 3rd 2009, 06:35 AM
  4. expansion, binomial
    Posted in the Algebra Forum
    Replies: 6
    Last Post: May 9th 2009, 10:22 AM
  5. Replies: 6
    Last Post: May 1st 2009, 11:37 AM

Search Tags


/mathhelpforum @mathhelpforum